Polyol Structure Influences Enzymatic Hydrolysis of Bio‐Based 2, 5‐Furandicarboxylic Acid (FDCA) Polyesters. Issue 9 (10th August 2017) - Haernvall, Karolina; Zitzenbacher, Sabine; Amer, Hassan; Zumstein, Michael T.; Sander, Michael; McNeill, Kristopher; Yamamoto, Motonori; Schick, Michael B.; Ribitsch, Doris; Guebitz, Georg M.
Abstract : Polyesters of 2, 5‐furandicarboxylic acid (FDCA) have gained attention as they can be regarded as the bio‐based alternatives to the petroleum‐based polyesters of terephthalic acid. However, only little is known about the biodegradation and enzymatic hydrolysis of FDCA‐based polyesters. This work aims to investigate the influence of different polyols on enzymatic hydrolysis of FDCA‐based polyesters. A series of polyesters containing various polyols are synthesized and analyzed regarding susceptibility to enzymatic hydrolysis by cutinase 1 from Thermobifida cellulosilytica (Thc_Cut1). FDCA‐based polyesters' number average molecular weight ( M n ) ranged from 9360–35 800 g mol −1 according to gel permeation chromatography (GPC) analysis. Differential scanning calorimetry (DSC) analyses show decreasing glass transition temperature ( T g ) with increasing diol chain length. Crystallinity of all polyesters is below 1% except for polyesters containing 1, 6‐hexanediol, 1, 8‐octanediol, and 1, 12‐dodecanediol for which calculated crystallinities are 27, 37, and 30%, respectively. Thc_Cut1 hydrolyzes all tested polyesters with preference for polyesters containing 1, 5‐pentanediol and 1, 9‐nonanediol (57.7 ± 7.5 and 52.8 ± 4.0% released FDCA). Enzyme activity increases when the linear diol 1, 3‐propanediol is replaced by the branched analog 1, 2‐propanediol or ethoxy units are introduced into the polyester chain. The results will contribute to expand the knowledge of microbial biodegradation of FDCA‐based polyesters. Abstract : A series of bio‐based 2, 5‐furandicarboxylic acid (FDCA)‐based polyesters are synthesized with various polyols via direct esterification, followed by investigating their susceptibility to enzymatic hydrolysis by cutinase 1 from Thermobifida cellulosilytica (Thc_Cut1). The influence of various polyols on enzymatic hydrolysis by Thc_Cut1 is studied in terms of released amount of FDCA. The results help overcome previous knowledge gaps on the enzymatic hydrolysis of FDCA‐based polyesters and is of larger interest given that FDCA‐based polyester have recently received increasing attention both in the scientific and industrial communities.